On the best approximations and Kolmogorov widths of besov classes of periodic functions of many variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Order estimates are obtained for the best approximations of the classesB 1, θ r in the spaceL q with 1